MANAJEMEN KANDANG PARTUS DAN LAKTASI PETERNAKAN ADHI FARM - , EKO SIDIQ MUSTOFA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The importance of management in a farm management consequences for the economic aspects, especially in the management of parturition and lactation in the cage Adhi farm livestock. In this scope includes financing the manufacture of cages, farm site selection, manufacture of cages, cage-making materials, maintenance cage. The results of the implementation of the Job Training was conducted on 24 February to 27 April 2014 in the pig farm Adhi Farm. The method used is a form of field observations interviews with sources is in charge of the farm and children's enclosure, data collection and follow the activities during field work practices in place. Based on the results of field practice management shows the management of cage farms are qualified. Because of ventilation, enclosure size, cleaning the cage, base enclosure, the enclosure wall, where food and drink is good. However, there are shortcomings in the manufacture of materials such as iron bars a cage woven often rusty and sharp, so often times injuring livestock and can cause illness due to rusted iron. The farm location is also less strategic because it is close to the residential and factory industru alcohol but, during fieldwork Peraktek odor from industrial waste does not affect the impact on livestock, only poses an unpleasant smell on breathe for the people if not used to it.